2019
DOI: 10.1155/2019/3531543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and pH on Early Hydration Rate and Apparent Activation Energy of Alkali-Activated Slag

Abstract: In order to investigate the effect of temperature and pH on the early hydration rate of alkali-activated slag (AAS), NaOH was used as alkali activator, and the nonevaporable water (NEW) content of the slag paste at different temperatures (5, 20 and 35°C) and pH (12.10, 12.55, 13.02, and 13.58) was measured. On the basis of the Arrhenius formula, the hydration rate of slag was characterized by the content of nonevaporative water, and the apparent activation energy of slag hydration at different pH was also obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…This further indicates that the measured system is far from a dissolution-controlled regime since it is known that the dissolution of a given material is highly dependent on the pH. This is supported by the work of Li et al, whose results indicate that the pH has a significant effect on the value of the E a for systems of alkali-activated slag in the range between pH 12 and pH 13.6, revealing an E a at 1 day in the range of 70–96 kJ/mol for a pH 12 and around 3 kJ/mol for a pH 13.6 [ 27 ].…”
Section: Discussionmentioning
confidence: 70%
“…This further indicates that the measured system is far from a dissolution-controlled regime since it is known that the dissolution of a given material is highly dependent on the pH. This is supported by the work of Li et al, whose results indicate that the pH has a significant effect on the value of the E a for systems of alkali-activated slag in the range between pH 12 and pH 13.6, revealing an E a at 1 day in the range of 70–96 kJ/mol for a pH 12 and around 3 kJ/mol for a pH 13.6 [ 27 ].…”
Section: Discussionmentioning
confidence: 70%
“…In addition, ∆H θ = and ∆S θ = also changed significantly when the H 2 O 2 concentration increased to 0.14 vol.%. Referring to the theoretical calculations and the experimental results in previous studies, E a is independent of reactant concentration, but is influenced by the change in reactants and the products of the oxidation reaction [39,[41][42][43][44]. It is therefore reasonable to infer according to the changes in E a that when the H 2 O 2 concentration is further increased to 0.14 vol.%, easier oxidation between chalcopyrite and H 2 O 2 can occur.…”
Section: Discussionmentioning
confidence: 91%
“…Gu et al 16 and Du et al 17 reported that the early reaction rate of AAS at low temperature (5–7°C) was slow, but the compressive strength of mortar cured for 3 days at 7°C reached 18.4 MPa. Samantasinghar and Singh 18 and Li et al 19 also stated that when the slag was activated with NaOH, the reaction rate of slag at the early age at low temperature was slow, especially for low alkali (pH ≤ 13.02) dosage.…”
Section: Introductionmentioning
confidence: 99%